PASSION AND PLAY a guide to designing sexual content in games. - Clough, Michelle ([S.l.] : CRC PRESS, 2022)
Hoping to add some steam and sex to your next game? Then this book is for you. This practical guide provides you with the foundational tools needed to write, design, and create healthy sexual content in video games in ways that are narratively compelling, varied, and hot! Challenging the assumptions that sex in games is superfluous, exploitative, or only of interest to straight guys, this book encourages designers to create meaningful, enjoyable sexual content for all audiences. Using examples from well-known AAA games (and some standout indie content!), each chapter provides a framework to guide game writers, designers, and developers through the steps of creating and executing sexual content in their games - from early concept, to setting it up in larger game narrative, and finally to executing specific sexual scenes and sequences. It also lays out a host of details and considerations that, while easily missed or forgotten, can have a major impact on the quality or theme of the scene. Offering expert insight and ideas for creating sex scenes in games, this book is vital reading for game designers, writers, and narrative designers who are interested in making games with sexual content. It will also appeal to artists, cutscene directors, audio engineers, composers, and programmers working on these games - or really, any game developer with an interest in the topic!
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Computer Science; Video games -- Social aspects; Sex